2021
DOI: 10.1021/acs.jproteome.1c00435
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Metabolomics and Network Pharmacology Reveal the Correlations between Constipation and Depression

Abstract: Constipation and depression are tightly related and often co-occur and coexist in clinic. Yet, the relationships and the underlying mechanisms are still unclear. Fecal metabolomics and network pharmacology were, for the first time, applied to investigate the potential correlations from multiple levels including classic behaviors, metabolomics, and gene targets. The behavioral indicators were analyzed, providing behavioral correlations at a macrolevel. Besides, fecal samples were analyzed by nuclear magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…44 A recent study revealed that the association between the two symptoms may be due to fecal metabolite pathways and common gene functional pathways. 46 Hence, physicians and psychologists can collaborate to provide appropriate pharmacological and psychological treatment for patients affected by depression or constipation. Alternatively, from the perspective of traditional Chinese medicine, qi (energy) stagnation syndrome shares commonalities with depression in Western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…44 A recent study revealed that the association between the two symptoms may be due to fecal metabolite pathways and common gene functional pathways. 46 Hence, physicians and psychologists can collaborate to provide appropriate pharmacological and psychological treatment for patients affected by depression or constipation. Alternatively, from the perspective of traditional Chinese medicine, qi (energy) stagnation syndrome shares commonalities with depression in Western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Next, excessive sleep duration always means decreased physical activity, an essential factor associated with a reduced risk of constipation ( 33 , 34 ). In addition, the indirect evidence from a meta-analysis indicates that excessive sleep time is significantly associated with increased depression risk, and depressed condition and functional constipation often co-occur and coexist in the clinic ( 35 , 36 ). Fourthly, the differential result among men and women reveals that abnormal sleep duration may also affect an intermediate factor, estrogen level, to impact further bowel movement, confirmed in animal experiments ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The faecal water content, gastric emptying rate, gastrointestinal ink push rate, and gastrointestinal hormones of gastrin (GAS) and motilin (MTL) were applied to characterise the gastrointestinal functions of rats. On top of this, each index was standardised, and then was applied to assess the associations among indexes related to depression and constipation, as previously described 16 …”
Section: Methodsmentioning
confidence: 99%
“…On top of this, each index was standardised, and then was applied to assess the associations among indexes related to depression and constipation, as previously described. 16 Sample collections of plasma and caecal contents After the last treatment of modelling, rats were immediately deprived of food but were allowed freely to drink. Afterward, faecal samples were collected for 12 h via metabolic cages.…”
Section: Animals and Experimental Designmentioning
confidence: 99%